Estrategias metodológicas para mejorar el proceso de enseñanza aprendizaje en los estudiantes del segundo de bachillerato en el área de electromecánica de la Unidad Educativa Ismael Pérez Pazmiño - Garces Punina, Segundo Manuel (2023)
The methodological learning strategies are the set of activities, techniques and means that are planned according to the needs of the population to which they are addressed, the objectives pursued and the nature of the areas and courses, all with the purpose of to make the learning process more effective. The profession of the mechanic demands a constant update of knowledge due to the fact that the automotive sector integrates more and more advanced electronic components that promise to make driving easier, but at the same time it becomes difficult for the workshops that continue to dominate traditional mechanics. and now they are forced to require the management of other added skills. The main challenges of this research project are to demonstrate the importance of methodological approaches, curricular design, didactic capacity and the resources used by teachers as significant elements to enhance the teaching-learning process in second year high school students in the electromechanical area. For the development of this research, the Inductive and Deductive methods were used. In addition, a survey is carried out that will allow obtaining certain information through the application of a series of questions. This investigative work aims to establish methodological strategies to improve the teaching-learning process in the students of the second year of high school in the area of electromechanics of the Ismael Pérez Pazmiño Educational Unit. Finally, the survey is applied as techniques, which will allow obtaining certain information through the application of a series of questions.